The Analysis of the Role of Usefulness, Trust, and Ease of Use in Driving Digital Banking Adoption in Indonesia - Alvinaldy Fitrah; Vanya Adisti; Christian Haposan Pangaribuan (Universitas Prasetiya Mulya, 2026)
Purpose - The purpose of this paper is to analyze the correlation of perceived usefulness, trust, and perceived ease of use towards the adoption of digital banking in Indonesia. Design/methodology/approach - A survey of the Indonesian population was conducted, and multivariate analysis was performed to discover linkages between respondents' perceptions and behaviour regarding digital banking. Findings - Trust and perceived usefulness have a substantial effect on digital banking adoption. On the contrary, perceived ease of use is insignificant towards digital banking adoption. Practical implications - The relationship between digital banking adoption and trust and perceived usefulness is strong which means banks should focus more on trust-building measures and improving digital banking usefulness to customers. Originality/value - In contrast to previous research, this paper reveals different results in the significance of perceived usefulness towards digital banking adoption.